3x(7x-3)=0

Divide each term in 3x(7x-3)=0 by 3.

3x(7x-3)3=03

Cancel the common factor.

3x(7x-3)3=03

Divide x(7x-3) by 1.

x(7x-3)=03

x(7x-3)=03

Divide 0 by 3.

x(7x-3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x=0

7x-3=0

Set the first factor equal to 0.

x=0

Set the next factor equal to 0.

7x-3=0

Add 3 to both sides of the equation.

7x=3

Divide each term by 7 and simplify.

Divide each term in 7x=3 by 7.

7×7=37

Cancel the common factor of 7.

Cancel the common factor.

7×7=37

Divide x by 1.

x=37

x=37

x=37

x=37

The final solution is all the values that make 3x(7x-3)3=03 true.

x=0,37

Solve Using the Square Root Property 3x(7x-3)=0